Contribution of dermal ethanol absorption during laboratory-controlled high-frequency use of alcohol-based hand rubs followed by glove use - Paul T. J. Scheepers; Kirsten Lassing; Martien H. F. Graumans; Sander H. P. Driessen; Antzelina Gkintsev; Ioanna Konstantinou; Valérie Leermakers; Hilde Onstek; Maxime Sülter; Lotte van den Oord; Chariya van Dolder; Hendrik Jan Jansen; et al. (Archives of Toxicology, 2026)
The safety of using ethanol-based products for hygienic hand disinfection in healthcare workers is controlled by restricting air levels. This raises the question of whether these workers are sufficiently protected against potential dermal absorption. The study aim was to determine the contribution of the dermal route to the total uptake of ethanol. A laboratory-controlled study of 25 sequential alcohol-based-hand-rubs (ABHRs) with subsequent intermediate glove use was conducted in seven healthcare workers. Two exposure conditions were compared: hands and forearms placed inside a laboratory fume hood preventing inhalation (skin-only condition) and the same procedure but outside the fume hood to allow inhalation (native condition). The hand hygiene product contained 84% ethanol and 1% ethanol-d6 added to verify exogenous origin. Inhalation exposure was measured by personal air sampling. Blood was collected at baseline, during exposure and a post-exposure wash-out period and analysed for ethanol and ethanol-d6 by HS-GC-MS. The contribution of dermal uptake was assessed by comparing the area-under-curve (AUC) of blood ethanol concentrations in the skin-only condition with that in the native condition within each study participant. Inhalation exposure in the breathing zone was (mean ± sd): 5.3 ± 3.6 mg/m 3 in the skin-only condition and 120 ± 7 mg/m 3 in the native condition. The corresponding AUCs for blood ethanol concentrations were 1400 ± 1100 and 3300 ± 2300 (mg/L)*min ( p = 0.014), respectively, indicating a contribution from dermal absorption of 43 ± 28% ( N = 7). For ethanol-d6 these values were 17 ± 4 and 48 ± 17 (mg/L)*min ( p = 0.064), respectively, with a contribution of dermal uptake of 40 ± 16% ( N = 3). In conclusion, high-frequency ABHRs lead to significant dermal absorption of ethanol.